Clinical benefits of vitamin A supplementation in infants and children with severe pneumonia - Prisca T.; J. S. Lisal; Azis Tanra; Dasril Daud (Indonesian Pediatric Society, 2007)
Background About 190 million preschool children living indeveloping countries are at risk of vitamin A deficiency. VitaminA deficiency and acute respiratory tract infection (ARI) are publichealth problems in developing countries. Children with vitaminA deficiency are more susceptible to measles, respiratory tractinfection, and other infections. Some studies show that vitaminA supplements may reduce the severity of respiratory tractinfection and other systemic complications of measles, anddiarrhea.Objective To evaluate the effect of vitamin A supplementation ininfants and children with severe pneumonia.Methods The study was a randomized trial on children with severepneumonia. Participants were randomly assigned to either receivevitamin A in addition to standard treatment (Group A), orstandard treatment alone (Group C). Time to achieve the normalrespiratory rate, time to achieve disappearance of subcostalretractions and fine rales were compared between the 2 groups.Result There was no significant difference in the achievement ofnormal respiratory rate between the vitamin group and the controlgroup (3.08 days vs 3.29 days). There was also no significantdifference in the disappearance of subcostal retractions amongthe two groups (2.30 days vs 2.48 days). However, there wassignificant difference in the disappearance of fine rales betweenthe two groups. The disappearance of fine rales in the vitamin Agroup occurred earlier (mean 3.72 days) than in the control group(mean 4.04 days) (P<0.01).Conclusions This study indicates that no significant difference inthe achievement of normal respiratory rate and disappearance ofsubcostal retractions between the vitamin A group as comparedto the control group, but there was a significant difference in thedisappearance of fine rales between two groups.